RESULTS OF A PETROGRAPHIC STUDY OF THE BRONZE AGE CASTING MOLDS FINDS - Nikitenko, І.; Starik, O.; Kutsevol, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The present article is devoted to the mineralogical and petrographic research of raw materials of the collection of casting molds of the Bronze Age, found by the expedition of Dnipropetrovsk National Historical Museum named after D.I. Yavornytskyi during the excavations of the archaeological monument of Tokivske-1, located near the village Tokivske of Apostolove Rayon, Dnipropetrovsk Oblast. The finding of casting molds is of great importance, since it can be the evidence of bronze foundry production existence in the territory of the monument, which until now was regarded only as a megalithic place of worship. Provenance determination of the raw materials of casting molds can help to identify the role of Tokivske-1 in the system of metalworking cells of the Sabatynivska culture time (XVI–XIII centuries BC) and to establish its links with the ancient centers of mining of stone raw materials. According to previous petrographic studies, it is known that stone molds were made mainly of talc-chlorite-tremolite schists, since this material was easily processed and could withstand more castings than clay molds. Because of this, stone casting molds were highly valued, as well as bronze wares and ingots, and were transported over long distances. The purpose of the study was to establish links between the archaeological monument of Tokivske-1 and known mining and metallurgical centers of the Bronze Age, on the basis of mineralogical and petrographic research of raw materials of casting molds. As a result of the study of samples in thin sections and by X-ray diffraction analysis, it was established that the stone molds were mainly made of tremolite-chlorite-anthophyllite meta-ultrabazites. The determination of the origin of the rocks from which the casting molds were made was carried out by comparing their mineralogical and petrographic features with the features of similar rocks that form natural outcrops, as described in geological survey reports and literary data, and as observed by us in rock samples from natural outcrops in the Middle Dnipro and the Azov Sea areas. It was ascertained that the rocks from which all the casting molds of the collection were made do not form natural outcrops in the Middle Dnipro area and are not characteristic of the Kryvyi Rih area, which is considered to be the main center of ISSN 1728–2713 ГЕОЛОГІЯ. 2(89)/2020 ~ 35 ~ raw materials extraction for the stone foundry forms of the Late Bronze Age on the territory of Ukraine. It was established that such rocks are more characteristic of the Western Azov Sea area, but one can not exclude another source of raw materials of the mold collection, in particular the Southern Urals, where bronze metallurgy was significantly developed and similar stone matrices were used. The obtained results suggest revision of established ideas on sources of supply of stone raw materials during the late Bronze Age.
Keywords: petrography; meta-ultrabasites; Ukrainian Shield; casting molds; Bronze Age